Installation and the Moving Image, Catherine Elwes (2015) - Knowles, Kim (Moving Image Review & Art Journal (MIRAJ), The, 2016)
Abstract New York and London: Wallflower Press and Columbia University Press, 304 pp., ISBN: 978 0 231 17451 0, p/bk, £19.00
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9taXJhai41LjEtMi4yNzZfNQ